A VICTIM OF AN EPIDEMIC OF POSSESSION SYNDROME - Chandrashekar, C. R. (Medknow Publications, 1981)
A case of young man who got possessed by a god and two spirits alternatively is reported. He was one of the four victims of an epidemic of possession by two spirits (Mohini). The epidemic occurred following the prediction that the two women who committed suicide, would become Mohinis and liaunt adult men. It appeared that the strong belief and expectation in the local culture made the index person who was otherwise well adjusted in life to get possessed. The implication of this finding is discussed.